Development Strategy of Taman Wisata Alam (TWA) Angke Kapuk, Penjaringan, North Jakarta - Rifqi Nur Amali (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2019)
The research was implemented in Taman Wisata Alam Angke Kapuk, North Jakarta on February - March 2016. The purpose of this research were to know and analyze: (1) profile of Taman Wisata Alam Angke Kapuk, (2) the existing internal and external factors of Taman Wisata Alam Angke Kapuk, (3) the proper development strategy and management based on the analysis of SWOT. Research methodology utilized in this study include;  descriptive research design, quantitative and qualitative type of data, primary and secondary source of data, incidental sampling technique, data collection using an observation, interview, questionnaire completion and documentation, and likert scale to measure the degree of visitors statement and opinion. Data analysis using SWOT and decision making using grand strategy matrix. The results revealed that the coordinate is at (0.72;1), which also means that it lies at Quadrant I. The findings showed that the suitable development strategy for Taman Wisata Alam Angke Kapuk of the current condition is the aggressive strategy  or SO strategy by making use all of strenghts to reach all possible opportunities.